THE ANALYSIS OF STUDENTSâ TEXT IN COOPERATIVE LEARNING ON THE STUDENTSâ RECOUNT TEXT MASTERY - Wulandari, Fitri (JURNAL SMART, 2016)
This study investigated the effects of studentsâ text in cooperative learning on studentsâ recount text mastery, and on their perfomance in their fisrt year classes at college. Seventy first year students of English Education Department STKIP Muhammadiyah Pringsewu Lampung (STKIP-MPL) in the academic of year 2014/2015 and a lecturer in the English Education Department of STKIP-MPL participated in this study. The data of this study came from two sources: a structured questionnaire and a set of semi-structured interviews. Descriptive statistics were used for analysis of the data coming from the questionnaire. Results indicated that studentsâ text in cooperative learning has some positive effects on studentsâ reading comprehension and on their perfomance in their first year classes at college.Keywords: studentsâ text, cooperative learning, recount text, reading comprehension